The power of powerful numbers - R. A. Mollin (International Journal of Mathematics and Mathematical Sciences)
In this note we discuss recent progress concerning powerful numbers, raise new questions and show that solutions to existing open questions concerning powerful numbers would yield advancement of solutions to deep, long-standing problems such as Fermat's Last Theorem. This is primarily a survey article containing no new, unpublished results.